Insuficiencia renal aguda inducida por rabdomiolisis (2016)
ABSTRACT: Acute renal failure is a frequent cause of morbidity and mortality in emergency, hospitalization and critical care services. In 15 % of cases it is due to rhabdomyolysis, in which there is breakdown of skeletal muscle with massive necrosis and leakage of muscle cell contents into the circulation. It has many different etiologies. The rhabdomyolysis-induced acute kidney injury results from the combination of several mechanisms, including tubular obstruction, vasoconstriction and oxidative stress. The most important therapeutic measures are: Aggressive repletion of fluids, forced diuresis and avoidance of exposure to nephrotoxic substances. In cases of severe uremia, metabolic acidosis, hiperkalemia or fluid overload it is necessary to start renal replacement therapy. As a rule, kidney function is completely recovered, but these patients have higher risk of future chronic kidney disease. Key words: Acute Renal Failure; Myoglobin; Necrosis; Rhabdomyolysis; Skeletal Muscles.